2016
DOI: 10.1038/srep20498
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the Plasmodium vivax transcriptome using RNA-Seq

Abstract: Historically seen as a benign disease, it is now becoming clear that Plasmodium vivax can cause significant morbidity. Effective control strategies targeting P. vivax malaria is hindered by our limited understanding of vivax biology. Here we established the P. vivax transcriptome of the Intraerythrocytic Developmental Cycle (IDC) of two clinical isolates in high resolution by Illumina HiSeq platform. The detailed map of transcriptome generates new insights into regulatory mechanisms of individual genes and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 73 publications
6
98
4
2
Order By: Relevance
“…To generate next generation sequencing libraries, we reverse‐transcribed mRNA from microdissected P. cynomolgi schizont and hypnozoite samples using the SMARTer Ultra Pico kit, amplified the resulting cDNA using long‐distance polymerase chain reaction, and constructed libraries compatible for Illumina sequencing. As a control and to enable direct comparison to the published P. vivax blood stage transcriptome (Bozdech et al, ; Westenberger et al, ; Zhu et al, ), we treated the P. cynomolgi blood stage samples that were used to infect A. stephensi mosquitoes in a similar manner. The sequencing reads were mapped simultaneously to the P. cynomolgi (PCYB v1.0) and M. fascicularis (v5.0) genomes using STAR (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate next generation sequencing libraries, we reverse‐transcribed mRNA from microdissected P. cynomolgi schizont and hypnozoite samples using the SMARTer Ultra Pico kit, amplified the resulting cDNA using long‐distance polymerase chain reaction, and constructed libraries compatible for Illumina sequencing. As a control and to enable direct comparison to the published P. vivax blood stage transcriptome (Bozdech et al, ; Westenberger et al, ; Zhu et al, ), we treated the P. cynomolgi blood stage samples that were used to infect A. stephensi mosquitoes in a similar manner. The sequencing reads were mapped simultaneously to the P. cynomolgi (PCYB v1.0) and M. fascicularis (v5.0) genomes using STAR (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…Although the molecular targets of TM2‐115 in hypnozoites remain uncharacterized, this study indicated that epigenetic regulation of gene expression may underlie hypnozoite quiescence. However, despite the availability of the genome of P. cynomolgi —which consists of ~5,700 genes presenting highly conserved synteny with P. vivax , but not with P. falciparum , distributed on 14 chromosomes (Tachibana et al, )—transcriptomic data are not available for any stage of P. cynomolgi , and in the case of P. vivax, studies have primarily focused on the blood stage transcriptome (Bozdech et al, ; Westenberger et al, ; Zhu et al, ). We therefore hypothesized that a systematic analysis of the transcriptome of P. cynomolgi schizonts and hypnozoites would allow for better understanding of hypnozoite quiescence and commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of transcriptional regulation in P. vivax are just beginning (36)(37)(38), some of the key biological processes that are thought to help P. vivax evade traditional control measures may be under tight transcriptional control. Unlike P. falciparum, P. vivax gametocytogenesis occurs early and concomitantly with the asexual cycle, so by the time a person is symptomatic or is diagnosed with P. vivax malaria, that person already harbors infectious gametocytes capable of infecting mosquitoes (39).…”
Section: Discussionmentioning
confidence: 99%
“…This family has a different copy number amongst Plasmodium species [15, 16]. These genes are expressed simultaneously but they are independently regulated [1720]. Functional assays have shown that P. falciparum MSP7 (MSP7I) is proteolytically processed; the resulting 22 kDa C-terminal region fragment is not covalently associated with MSP1 [7] and has cross-reactivity with other MSP7 proteins [17].…”
Section: Introductionmentioning
confidence: 99%